2013
DOI: 10.1002/app.39443
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of fullerene functionalized poly(vinyl chloride) (PVC) and dehydrochlorinated PVC using atom Transfer Radical Addition and AIBN based fullerenation

Abstract: The research presented details chemical modifications of poly(vinyl chloride) (PVC) and its derivative, dehydrochlorinated PVC (DH-PVC) through the use of two grafting techniques, namely a normal fullerenation, using AIBN (2,2 0 -Azoisobutyronitrile), and the atom transfer radical addition (ATRA). The products were characterized and the presence of new FTIR peaks at 528 and 577 cm 21 along with new 1 H-NMR signal at 3.9 ppm, suggested that fullerenes has been grafted to the polymer molecules. Percentage of C 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…As shown in Fig. 1a, the characteristic peaks of the PVC molecules can be seen; including peaks for C-H bands (1,427 and 1,257 cm −1 ), C-C vibrations (968 cm −1 ), and C-Cl bands (698, 636 and 605 cm −1 ) 24 . Also, the spectra show the peak at 1,732 cm −1 which corresponds with the carbonyl group (C = O) bands in the DBA and PVC gels.…”
Section: Resultsmentioning
confidence: 90%
“…As shown in Fig. 1a, the characteristic peaks of the PVC molecules can be seen; including peaks for C-H bands (1,427 and 1,257 cm −1 ), C-C vibrations (968 cm −1 ), and C-Cl bands (698, 636 and 605 cm −1 ) 24 . Also, the spectra show the peak at 1,732 cm −1 which corresponds with the carbonyl group (C = O) bands in the DBA and PVC gels.…”
Section: Resultsmentioning
confidence: 90%
“…Figure 3(B) shows FT‐IR spectra of pure PVC gel and PVC/f‐rGO composite gels. The main characteristics bands were observed at 3448–3454, 2860–2970, 1740–1780 cm −1 , and 750 and 633 cm −1 are attributed to (‐NH,‐OH), –CH 2 , carbonyl group (C=O) of DBA and ‐Cl of PVC, 39–41 respectively. We found that by increasing the loading of f‐rGO in the PVC gel, the peaks havebecome broader and shifted to higher wave numbers as shown in Figure 3(B).…”
Section: Resultsmentioning
confidence: 99%
“…PVC and its dehydrochlorinated (DHPVC) form were tagged with fullerene C 60 under normal procedure (AIBN as initiator) and atom transfer radical addition methodology (ATRA) in THF at 80 °C for 24 h (Eq. 31) [117]. The grafted C 60 extents on PVC were 5.66 and 2.77% for ATRA and AIBN methods, respectively; that for grafted onto DHPVC using AIBN was 4.65%.…”
Section: Functionalization By Carbon Allotropesmentioning
confidence: 93%